ACONSELHAMENTO PASTORAL E LOGOTERAPIA Convergências Possíveis Frente ao Suicídio - Silva, Vardilei Ribeiro da (2021)
The subject of suicide has long been a big taboo. The roots of this taboo lie in the medieval period, when the death of oneself was considered a crime against God, the physical punishments for suicidal bodies were unreasonable and, in addition to the bodies, souls were summarily condemned to hell due to the attempt on life. It is understood, therefore, why even today the theme generates discomfort in Western society based on the values of the Christian religion, an opinion-forming religion and a promoter of actions against suicides in the medieval context. Without fear of knowing the phenomenon of suicide, the research that is presented sought to dialogue with the different areas of human knowledge in order not only to better understand the phenomenon of suicide, but also the different areas of knowledge that support the meaning of life without, however, relying on religious moralism that ignores the conditions underlying suicide. In this search for knowledge, research is concerned with enabling Pastoral Counseling with people with suicidal ideas to present themselves in a humanized way, making people aware of their responsibility for life. In this sense, the contributions of Logotherapy are relevant to Pastoral Counseling in our context so marked by suffering that it provides an existential void.